Implementasi Bandung Smart City Untuk Mewujudkan Smart Tourism Destination - Bachrian, Fauzan Akbar; Suryawan, Ida Bagus (JURNAL DESTINASI PARIWISATA, 2021)
The Smart City of Bandung city is one of the best in Indonesia because it has received various awards of Smart City from Asia’s Tech Ecosystem Magazine 2015, the Smart City of Bandung City was established in 2016 and has had plans since 2013. The research aims to see whether the smart city in its implementation can make Smart Tourism Destinations in Banduung City. This research uses two data sources, namely primary data and secondary data. The data collection techniques in this research are documents. The analysis technique used is Data reduction, data presentation, and verification and drawing conclusions. The results of this research are to see existing conditions that have been carried out since Smart City has been implemented in Bandung City as well as seeing the implementation of Smart City in making Bandung City a Smart Tourism Destination. Keyword: Smart City, Smart Tourism Destination, Kota Bandung